2020
DOI: 10.2169/internalmedicine.3715-19
|View full text |Cite
|
Sign up to set email alerts
|

Vonoprazan-associated Gastric Mucosal Redness: A Report of Four Cases

Abstract: To date, no cases of vonoprazan-associated gastric mucosal redness have been reported, and its endoscopic and pathological features remain largely unclear. We report four cases of vonoprazan-associated gastric mucosal redness. In all cases, esophagogastroduodenoscopy (EGD) demonstrated linear or spotty redness that newly appeared in the greater curvature of the middle gastric body after the initiation of vonoprazan, which disappeared after its discontinuation. A tissue biopsy taken from the gastric mucosa with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Second, vonoprazan-associated gastric mucosal redness is associated with various pathological findings. Our study confirmed the presence in our cases not only of inflammatory cell infiltration, PCPs, and oxyntic gland dilatation, in agreement with an earlier report [ 5 ], but also of congestion, focal hemorrhage with congestion beneath the basement membrane, and vacuolar degeneration of parietal cells, as new findings. A tissue biopsy specimen taken from the site from which spotty and linear redness had disappeared revealed improvement in focal hemorrhage, with congestion shown to be present in all 4 patients (100%), inflammatory cell infiltration in 2 patients (50%), and PCPs and oxyntic gland dilatation in 2 patients (50%).…”
Section: Discussion/conclusionsupporting
confidence: 94%
See 2 more Smart Citations
“…Second, vonoprazan-associated gastric mucosal redness is associated with various pathological findings. Our study confirmed the presence in our cases not only of inflammatory cell infiltration, PCPs, and oxyntic gland dilatation, in agreement with an earlier report [ 5 ], but also of congestion, focal hemorrhage with congestion beneath the basement membrane, and vacuolar degeneration of parietal cells, as new findings. A tissue biopsy specimen taken from the site from which spotty and linear redness had disappeared revealed improvement in focal hemorrhage, with congestion shown to be present in all 4 patients (100%), inflammatory cell infiltration in 2 patients (50%), and PCPs and oxyntic gland dilatation in 2 patients (50%).…”
Section: Discussion/conclusionsupporting
confidence: 94%
“…The endoscopic features of vonoprazan-associated gastric mucosal redness in the earlier report were spotty or linear redness in the greater curvature of the gastric body [ 5 ]. It had not been previously observed, newly appeared at least 2 months after initiation of the drug, and disappeared at least 3 months after discontinuation of the drug.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric mucosal changes that may be specific to vonoprazan were mucosal erythema in only four patients. 18 Recently, we detected small white protrusions in a patient's stomach at endoscopy. This differs from other known endoscopic findings such as xanthoma and white globe appearance.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Kubo et al ( 4 ) reported a novel lesion which they termed ‘gastric mucosal redness’ in patients undergoing VPZ therapy in a case series. Gastric mucosal redness was characterized by linear or spotty red areas along the greater curvature of the gastric body.…”
Section: Introductionmentioning
confidence: 99%